Determinant Factors of Hypertension in pre-geriatric group (18-35 years old) in Surabaya - Minarni Wartiningsih (Universitas Airlangga, 2019)
Background: Hypertension data based on age groups in Surabaya showed an increase in hypertension trends in the young age group. It is known that hypertension risk factors are gender, behavior or lifestyle, age, sex, race/ethnicity, genetics, effective stress management, and obesity. Of all these risk factors, behavioral factors or specifically referred to as lifestyle are closely related to hypertension morbidity in the aged 18-35 years. Objective: The aims of this study is to determine the determinants that most influence the incidence of hypertension in order to reduce the prevalence of hypertension at 18-35 years old in the western and eastern parts of the city of Surabaya. Method: This studi employed cross-sectional observational analysis using Chi Square and logistic regression. Sample of this studi were 404 respondents taken by Cluster Random Sampling, with inclusion criteria as follows: 18-35 years old, currently not in hypertension medication, never having a stroke and suffering from a heart condition. The respondent's blood pressure check is carried out before and after completing the questionnaire. Results: The results of research shows unfavorable behavior towards healthy lifestyle, smoking behavior, exercise, fast food consumption, stress, and sleep time have significant results on the incidence of hypertension. Of all factors, smoking behavior was the highest (p = 0,000; OR 14,366). Conclusion: To prevent an increase in the prevalence of hypertension in 18-35 years, it is necessary to implement regulation of non-smoking area.